Direct and moderating effects of organizational factors on system usage in colleges: a resource-based perspective - Faridiah Aghadiati Fajri; Nurisqi Amalia (Jurnal Akuntansi dan Auditing Indonesia, 2018)
Colleges as a non-profit organization engaged in the educational sector have a crucial role, especially in emerging countries. Significant improvement can be achieved by continuously strengthening the information system infrastructure. Prior studies mentioned the system implementation is tricky because it involves not only hardware and software but also users and operational procedures. The investment of information system poses challenges for management. The system failure can be the grave of an organization. Therefore, the end-users participation becomes acute that puts organizational factors have to be considered. This study aims to examine and analyze the information system success model by adding the existence of facilitating condition, institutional pressure, and incentives as organizational factors. Data were obtained through questionnaires filled by the users of colleges’ system. The results found that two constructs of organizational factors including facilitating condition and institutional pressure were able to increase the role of system usage to organization performance. Managers have to be proactive to motivate the end-users by designing better organizational factors and the future study may improve the construction of these factors.